Peran Ustadz dalam Pembinaan Keagamaan Masyarakat Muslim Dusun II Desa Tuntungan II, Pancur Batu, Deli Serdang - Julisnawati Siregar; Faisal Riza; Aulia Kamal (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research aims to analyze the role of ustadz in religious development of the Muslim community in Dusun II, Tuntungan II Village, Pancur Batu District, Deli Serdang Regency. The Ustadz has a central role in guiding the community in religious matters, both through teaching, guidance in worship, and strengthening morals and Islamic values. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, observation and documentation studies. This research found two things; Firstly, in the social structure of the Tuntungan village community, the ustadz has an important position, not only as a spiritual leader who provides religious guidance, but also as the main pillar in maintaining social harmony and strengthening religious values ​​in society. Second, the Ustadz plays an important function in cultivating Islamic teachings in the practice of daily life, he acts as a catalyst for change in society, as well as penetrating various social problems faced by society. Therefore, there is a need for further support from various parties, including the government and religious organizations, to strengthen the role of ustadz in religious formation